A TCR mechanotransduction signaling loop induces negative selection in the thymus. (December 2018) - Hong, Jinsung; Ge, Chenghao; Jothikumar, Prithiviraj; Yuan, Zhou; Liu, Baoyu; Bai, Ke; Li, Kaitao; Rittase, William; Shinzawa, Miho; Zhang, Yun; Palin, Amy; Love, Paul; et al.
Abstract The T cell antigen receptor (TCR) expressed on thymocytes interacts with self-peptide major histocompatibility complex (pMHC) ligands to signal apoptosis or survival. Here, we found that negative-selection ligands induced thymocytes to exert forces on the TCR and the co-receptor CD8 and formed cooperative TCR–pMHC–CD8 trimolecular 'catch bonds', whereas positive-selection ligands induced less sustained thymocyte forces on TCR and CD8 and formed shorter-lived, independent TCR–pMHC and pMHC–CD8 bimolecular 'slip bonds'. Catch bonds were not intrinsic to either the TCR–pMHC or the pMHC–CD8 arm of the trans (cross-junctional) heterodimer but resulted from coupling of the extracellular pMHC–CD8 interaction to the intracellular interaction of CD8 with TCR–CD3 via associated kinases to form a cis (lateral) heterodimer capable of inside-out signaling. We suggest that the coupled trans–cis heterodimeric interactions form a mechanotransduction loop that reinforces negative-selection signaling that is distinct from positive-selection signaling in the thymus. Zhu and colleagues show that negative-selection ligands induce cooperative TCR–pMHC–CD8 trimolecular 'catch bonds', whereas positive-selection ligands induce TCR–pMHC and pMHC–CD8 bimolecular 'slip bonds'.